The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1515/auto-2018-0064
|View full text |Cite
|
Sign up to set email alerts
|

Improving reliability and latency of Wireless Sensor Networks using Concurrent Transmissions

Abstract: Concurrent Transmissions (CT) based flooding appears as a highly reliable and low latency mechanism to achieve source-to-sink communication of packets within a Wireless Sensor Network (WSN). CT are usually misunderstood, since they are mainly analyzed in the baseband domain. A comprehensive analysis, including the effects of the carrier, demonstrates that they cannot work in simple phase-modulated communication systems due to the beating effect. In contrast, non-coherent frequency receivers offer a very robust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 3 publications
0
15
0
Order By: Relevance
“…The benefit of this approach, key to the operation of Atomic-SDN, is that it allows the protocol to be temporally decoupled from normal network operation; VOLUME x, 2019 allowing it to be run alongside other control and application protocols or, as in the case of Atomic-SDN, be used to regularly configure those protocols. Multiple Initiators: Subsequent studies to the original Glossy paper have shown that the receiver is able to reliably demodulate multiple concurrent transmissions of the same data not necessarily because of so-called constructive interference, as the authors first considered, but likely as a result of transmissions being demodulated as non-coherent Minimum-Shift Keying (MSK), as well as Direct Sequence Spread Spectrum (DSSS) minimizing the error rate [27]- [29].…”
Section: B Concurrent Transmissions and Synchronous Floodingmentioning
confidence: 99%
“…The benefit of this approach, key to the operation of Atomic-SDN, is that it allows the protocol to be temporally decoupled from normal network operation; VOLUME x, 2019 allowing it to be run alongside other control and application protocols or, as in the case of Atomic-SDN, be used to regularly configure those protocols. Multiple Initiators: Subsequent studies to the original Glossy paper have shown that the receiver is able to reliably demodulate multiple concurrent transmissions of the same data not necessarily because of so-called constructive interference, as the authors first considered, but likely as a result of transmissions being demodulated as non-coherent Minimum-Shift Keying (MSK), as well as Direct Sequence Spread Spectrum (DSSS) minimizing the error rate [27]- [29].…”
Section: B Concurrent Transmissions and Synchronous Floodingmentioning
confidence: 99%
“…In fact, the time required for data collection varies owing to different data collection strategies. According to the different MAC protocol used in data collection, it can be divided into contentionbased data collection mechanisms [1], [9], [13], [26], [32], [36] and non-contention based data collection mechanisms [4], [7]. The non-contention MAC protocol is represented by the Time Division Multiple Access (TDMA) protocol [4], [7].…”
Section: Related Workmentioning
confidence: 99%
“…The non-contention MAC protocol is represented by the Time Division Multiple Access (TDMA) protocol [4], [7]. Most of the data collection protocols adopt are contentionbased protocols [1], [9], [13], [26], [32], [36]. The main feature of the non-contention data collection protocol represented by the TDMA protocol is that the time is divided into units called slots.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations